2015
DOI: 10.1007/s00784-015-1658-2
|View full text |Cite
|
Sign up to set email alerts
|

Early-life factors affect risk of pain and fever in infants during teething periods

Abstract: Knowledge of prevalence and risk factors of teething disturbances may better equip primary caregivers and healthcare professionals to accurately detect teething-related local and/or systemic signs/symptoms and effectively facilitate tobacco cessation among pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…Approximately 6% of infants were given NHPs for the same purpose. The prevalence of analgesic use in our study aligns with rates of 36–50% for teething pain or fever found in other infant populations [ 32 ]. North American physicians frequently recommend analgesics or teething rings for infant teething symptoms, whereas NHPs (e.g., homeopathic drops) are more often prescribed by French pediatricians [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…Approximately 6% of infants were given NHPs for the same purpose. The prevalence of analgesic use in our study aligns with rates of 36–50% for teething pain or fever found in other infant populations [ 32 ]. North American physicians frequently recommend analgesics or teething rings for infant teething symptoms, whereas NHPs (e.g., homeopathic drops) are more often prescribed by French pediatricians [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…In a cohort study of passive smoking in Singapore, the prevalence of teething pain in infants was significantly associated with their mothers’ exposure to passive smoking during early pregnancy [ 55 ]. Another study reported that intrauterine exposure to tobacco smoke was associated with the pain perception levels of newborns, as determined during routine vaccination injections given at 48 h after birth [ 56 ].…”
Section: Clinical Questionsmentioning
confidence: 99%
“…The practice of IOM takes place during a child’s growth period of 4–18 months, which largely coincides with the age of 6 months when the child’s immune system matures from the mother’s passive immunity to self-innate immune system. The period also coincides with the time when the child weans from the mother’s breast milk, as well as with the ‘teething’ period, when the child is usually exposed to external pathogens that can result in non-specific symptoms such as vomiting, diarrhoea, pain and fever,6 symptoms that are also known to be associated with IOM. Among the international dental and indigenous tribal communities, IOM is known by other alternative terms: tooth bud gouging,6 germectomy,7 nylon teeth mutilation, ‘Ebinyo’/‘Ebiino’/‘Ebino’/‘Nylon teeth’,8 ‘Two lak’/‘telak’/‘Gidog’,9 ‘Lugbara tooth’ and ‘Haifat’ 10.…”
Section: Facts and Myths About Infant Oral Mutilationmentioning
confidence: 90%
“…The period also coincides with the time when the child weans from the mother’s breast milk, as well as with the ‘teething’ period, when the child is usually exposed to external pathogens that can result in non-specific symptoms such as vomiting, diarrhoea, pain and fever,6 symptoms that are also known to be associated with IOM. Among the international dental and indigenous tribal communities, IOM is known by other alternative terms: tooth bud gouging,6 germectomy,7 nylon teeth mutilation, ‘Ebinyo’/‘Ebiino’/‘Ebino’/‘Nylon teeth’,8 ‘Two lak’/‘telak’/‘Gidog’,9 ‘Lugbara tooth’ and ‘Haifat’ 10. Although the prevalence of IOM has varied within and without countries where it is practised, some of the documented ones have been from Ethiopia (38%–70%),4 Tanzania (0.5%–37%),8 Uganda (2%–30%),2 South Sudan (70%–100%)11 and Kenya (37%–87%) 12.…”
Section: Facts and Myths About Infant Oral Mutilationmentioning
confidence: 90%